Responding to change a community analysis on information needs and a perspective on public library establisment in Barangay Sevilla, Sta. Cruz, Ilocos Sur - Turgano, Ma. Estrella Javillonar (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This is a community analysis study of the information needs of Barangay Sevilla, Sta. Cruz, Ilocos Sur that aims to find out the residents' perspectives on public library establishment. This study reveals that residents preferred printed information materials such as books, school books, newspapers and reference materials over information obtained from electronic media, such as the Internet. The weak preference for the Internet and other electronic services is due to the lack of electronic services in the Barangay and the lack of awareness of the respondents regarding its usage. Despite the presence of a variety of information materials in the barangay, respondents generally agreed that adequate information is highly inaccessible to the respondents. Posing a barrier to information access is the geographical distance of the nearest public library thus reducing the motivation of the respondents to search for the needed information.